Stock performance of Jakarta Islamic Index based on sharpe, Treynor and Jensen method - Edi Susilo; Ainun Najah (Jurnal Ekonomi dan Keuangan Islam, 2018)
This study aims to analyse stock performance using the Sharpe, Treynor and Jensen methods at Jakarta Islamic Index during 2014-2016. This research is a descriptive and quantitative research. The object of the research is the stocks listed on Jakarta Islamic Index in the period of 2014 to 2016. The sample selection is determined by purposive sampling technique with the criteria of stocks consistently listed on Jakarta Islamic Index during 2014-2016. By this criteria, this study used 19 stocks as a sample. The result shows that there is no stock that consistently performed positively or consistently outperformed Jakarta Islamic Index against market benchmark.